2008
DOI: 10.2478/v10011-008-0019-y
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Urinary Markers in the Evaluation of Diabetic Nephropathy

Abstract: The Significance of Urinary Markers in the Evaluation of Diabetic Nephropathy Oxidative stress is considered to be a unifying link between diabetes mellitus (DM) and its complications, including nephropathy (DN). The aim of this study was to determine the parameters of oxidative injury of lipids and proteins as well as the activity of ectoenzymes in the urine of DN patients. The study included 40 individuals: 10 patients with type 2 diabetes mellitus and microalbuminuria (DMT2-MIA), 10 type 2 diabetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The urinary TBARS and RCD levels may refer to an oxidative damage occurring in the kidney ( 10 ). Previous studies as well indicated that renal transplant recipients had higher TBARS levels than healthy individuals ( 8 , 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The urinary TBARS and RCD levels may refer to an oxidative damage occurring in the kidney ( 10 ). Previous studies as well indicated that renal transplant recipients had higher TBARS levels than healthy individuals ( 8 , 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…The protein oxidation level was monitored by a spec-trophotometric determination of carbonyl content by the method of Levine et al ( 13 ) using 2,4-dinitro-phenylhydrazine (DNPH) as a classic carbonyl reagent. Spectrophotometric measurement of reactive carbonyl derivates (RCD) values was performed and calculated using the extinction coefficient of DNPH-reactive carbonyl derivates at 370 nm and expressed as μmol/mmol creatinine ( 10 ). Urinary N-acetyl-β-d-glucosaminidase (NAG) activity was determined according to the method of Horak et al ( 14 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies also showed that the monitoring of NAG urine activity is useful in the evaluation of early proximal tubule damage (31) and in predicting the long-term function of the transplanted kidneys recipients ( 32 , 33 ).…”
Section: Biomarkers After Organ Transplantation and Risk Managementmentioning
confidence: 99%
“…It has been shown that early renal tubular damage is characterized by increased proximal tubular enzymuria. [17][18][19][20][21][22] However, contradictory findings were noted. 15,23 Hence it needs to be further studied.…”
Section: Introductionmentioning
confidence: 99%